Spatial structure counts : the relevance of regional labour-market conditions for educational transitions to vocational training - Weßling, Katarina [Verfasser]; Hartung, Andreas [Verfasser]; Hillmert, Steffen [Verfasser] (My University, 2015)
"Regional context conditions can have a crucial impact on school-to-work transitions and subsequently individual life chances. This paper aims to develop an approach to analyse the spatial references of regional socio-economic contextual settings young adults are embedded in. We apply this approach to assess the impact of regional unemployment on the transition from lower or intermediate compulsory schooling to vocational education and training (VET) in Germany. We use data from the German Socio-Economic Panel Study (GSOEP) and merge these with administrative time series data on NUTS 3-regions level. We attach geocodes to the administrative districts to allow for a flexible operationalisation of the spatial reference of regional socio-economic contextual settings. Our results indicate, first, a negative relation between regional unemployment and the chances of entering vocational training in the dual system. Second, the effects of unemployment on adolescents' transition chances have a specific spatial structure: The labour-market situation in the respondent's district of residence moderates the relation between the labour-market situation in surrounding districts and the school graduates' chances of entering dual training." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; G 1.2.2.4 Arbeitslosigkeit; T 3.5 Statistik; Duales System; Berufseinmündung; Erste Schwelle; Einflussfaktor; Arbeitslosigkeit; Regionale Verteilung; Empirische Untersuchung; Sozioökonomisches Panel